2020
DOI: 10.4322/acr.2020.178
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Myxoma An unusual cause of ischemic stroke in young

Abstract: Atrial myxomas are rare primary cardiac tumours with neurological manifestations being reported in 30% of cases. Though a rare cause of ischemic stroke in young patients, considering it as a possibility in absence of any obvious risk factors can help avoid misdiagnosis at early stages. We present a case of left atrial myxoma in a 36-year-old male with no known co-morbidities, showing an unusual clinical presentation of isolated bilateral painless vision loss. With multiple infarcts on Non Contrast Computerised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Moss et al reported a case of cardiac myxoma in a middle-aged patient who presented with sudden left-sided paresis and paresthesia and was diagnosed with multifocal ischemic strokes [ 9 ]. Sohal et al also underlined a case of ischemic stroke in a young patient caused by cardiogenic emboli from an atrial myxoma [ 10 ]. The underlying pathophysiological mechanism of cardiac myxoma as an etiology of ischemic stroke is the friable and gelatinous nature of the tumor component, which can dislodge from the tumor causing embolization to distant areas.…”
Section: Discussionmentioning
confidence: 99%
“…Moss et al reported a case of cardiac myxoma in a middle-aged patient who presented with sudden left-sided paresis and paresthesia and was diagnosed with multifocal ischemic strokes [ 9 ]. Sohal et al also underlined a case of ischemic stroke in a young patient caused by cardiogenic emboli from an atrial myxoma [ 10 ]. The underlying pathophysiological mechanism of cardiac myxoma as an etiology of ischemic stroke is the friable and gelatinous nature of the tumor component, which can dislodge from the tumor causing embolization to distant areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reappearance of such a correlation suggests the need to extend research in this direction. Myxoma of the heart often manifests as heart failure or the effect of embolic complications, most often affecting the cerebral vessels, but also the pulmonary, renal, coronary, and lower limb vessels (15,16) . The symptoms described in the medical literature include shortness of breath, hemiparesis, arrhythmias, fainting, nausea, weight loss, and even sudden death (1,11) .…”
Section: Discussionmentioning
confidence: 99%
“…Though elevation of erythrocyte sedimentation rate, C-reactive protein with anemia, and hyperglobulinemia is often seen in active illness, magnetic resonance imaging (MRI) of the brain and trans-oesophageal echocardiography are the diagnostic imaging modality of choice [2,8]. These myxomatous emboli can rarely cause aneurysms by infiltrating the vessel walls [9]. Annual follow-up is recommended with echocardiography for three to four years of post-surgical removal due to the chances of recurrence and also to look for metastasis [10].…”
Section: Discussionmentioning
confidence: 99%